Temporal trends in stroke incidence in South Asian, Chinese and white patients: A population based analysis - Khan, Nadia A. (PLoS One, 2017)
BACKGROUND: Little is known about potential ethnic differences in stroke incidence. We compared incidence and time trends of ischemic stroke and primary intracerebral hemorrhage in South Asian, Chinese and white persons in a population-based study. METHODS: Population based census and administrative data analysis in the provinces of Ontario and British Columbia, Canada using validated ICD 9/ICD 10 coding for acute ischemic and hemorrhagic stroke (1997–2010). RESULTS: There were 3290 South Asians, 4444 Chinese and 160944 white patients with acute ischemic stroke and 535 South Asian, 1376 Chinese and 21842 white patients with intracerebral hemorrhage. South Asians were younger than whites at onset of stroke (70 vs. 74 years for ischemic and 67 vs. 71 years for hemorrhagic stroke). Age and sex adjusted ischemic stroke incidence in 2010 was 43% lower in Chinese and 63% lower in South Asian than in White patients. Age and sex adjusted intracerebral hemorrhage incidence was 18% higher in Chinese patients, and 66% lower in South Asian relative to white patients. Stroke incidence declined in all ethnic groups (relative reduction 69% in South Asians, 25% in Chinese, and 34% in white patients for ischemic stroke and for intracerebral hemorrhage, 79% for South Asians, 51% for Chinese and 30% in white patients). CONCLUSION: Although stroke rates declined across all ethnic groups, these rates differed significantly by ethnicity. Further study is needed to understand mechanisms underlying the higher ischemic stroke incidence in white patients and intracerebral hemorrhage in Chinese patients.